Identification and mapping the high nature value farmland by the comparison of a combined and species approaches in Tuscany, Italy - Lazzerini, Giulio; Dibari, Camilla; Merante, Paolo; Pacini, Gaio Cesare; Moschini, Valentina; Migliorini, Paola; Vazzana, Concetta (Italian Journal of Agronomy, 2015)
Low-intensity farming systems play a crucial role in nature conservation by preserving 50% of habitats, flora and fauna occurring in Europe. For this reason the identification, classification and mapping of high nature value farmlands (HNVfs) is becoming an overriding concern. In this study, two different approaches, namely combined approach and species-based approach, were used to spatially identify HNVfs (type 1, 2 and 3) across Tuscany region (Italy). The first approach calculated different indicators (extensive practices indicator, crop diversity indicator, landscape element indicator) at 1Ã—1 km grid cell spatial resolution using pre-existent spatial datasets integrated within a global information system environment. Whilst, the speciesbased approach relied on a pre-existent regional naturalistic inventory. All indicators and the resulting HNVfs derived from the two approaches were aggregated at municipality level. Despite some difference, the two adopted approaches intercepted spatially the same HNVfs areas, accounting for 35% of the total utilised agricultural area of the region. Just 16% of HNVfs resulted located inside protected areas, thus under current conservation and protection management actions. Finally, HNVfs of the Tuscany region were spatially aggregated in four relevant agro-ecosystems by taking into consideration the cropping systems and the landscape elementsâ€™ characteristics peculiar in the region.